A woodland wedding - Elliott, Rebecca (New York, NY Scholastic Inc., 2016)
Eva's teacher, Miss Featherbottom, is getting married, but when her special necklace disappears, Eva and her friends set out to track down the thief and return the necklace before the wedding.
Horn Book, April 2017
K-3
2.1.
Accelerated Reader AR
Keywords: School stories; Weddings -- Fiction; Theft -- Fiction; Teachers -- Fiction; Owls -- Fiction